(untitled) (European Journal of Pure and Applied Mathematics, 2025)
A numerical analysis was performed on the steady-state magnetohydrodynamics of a tangent hyperbolic nanofluid (THNF) flowing over a vertically expanding surface with nonlinear expansion. This study examines the influence of factors such as sheet thickness variation, Darcy number, magnetic field, heat source/sink, thermal conductivity, viscous dissipation, and thermal radiation on THNF flow behavior. The THNF model, classified as a non-Newtonian fluid, is widely utilized in laboratory settings and industrial machinery for the management of excessive heat. The governing equations were non-dimensionalized and transformed into a system of ordinary differential equations (ODEs) using similarity variables to evaluate the flow. The ordinary differential equations were solved numerically using the MATLAB BVP4C solver. A comparative evaluation was conducted to assess the accuracy of the results. Graphical analysis demonstrated that activation energy increases the mass transfer rate, while chemical reactions typically reduce it. The research also demonstrated that the Weissenberg number, Brownian motion, and Rayleigh number collectively increase the fluid temperature. Additionally, increasing the Darcy number and thermal radiation improved fluid flow and heat transfer rates, respectively. Skin friction increased with higher and magnetic field intensity, even though the rate of energy transmission decreased.